Preface - Demenko, Grazyna (Archives of Acoustics, 2007)
The Polish Phonetic Association have the great pleasure to give the "Archives of Acoustic" Readers possibility acquaint with topics presented at the conference Applicationsof Phonetic Research to Speech Analysis, Synthesis and Recognition, whichwas held in 2005 in Kraków, and the conference Speech Signal Annotation, Processingand Synthesis organised by Department of Phonetics Adam Mickiewicz Universityin Pozna´n, and Institut für Kommunikationswissenschaften in Bonn, and supported byAlexander von Humboldt Stiftung under auspices: The International Speech CommunicationAssociation ISCA and Polish Phonetic Association.